The economics of devaluation and the Nigerian economic crisis - Iornem, David (Markurdi : New Idea Limited, 1982)
This volume consist of conference proceedings at the National Conference on the future of the Naira held under the auspices of the New Idea Limited, Management Consultants in Markurdi on July 10, 1982.
lje 15/03/2019
Arch.
Keywords: Economic conditions; Devaluation of currency; Naira; Nigeria